2017
DOI: 10.1093/mnras/stx3222
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning search for variable stars

Abstract: Photometric variability detection is often considered as a hypothesis testing problem: an object is variable if the null-hypothesis that its brightness is constant can be ruled out given the measurements and their uncertainties. The practical applicability of this approach is limited by uncorrected systematic errors. We propose a new variability detection technique sensitive to a wide range of variability types while being robust to outliers and underestimated measurement uncertainties. We consider variability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 110 publications
1
51
0
Order By: Relevance
“…Objects for which the classifications differ will be inspected and added to the training sample with it's correct label. After we have created a sizable training sample, we will experiment with more sophisticated classifiers like stochastic gradient boosting (Chen & Guestrin 2016) and neural networks (e.g., LeCun et al 2015) which have been shown to perform better than random forest (Pashchenko et al 2018).…”
Section: Classification Of Periodic Variablesmentioning
confidence: 99%
“…Objects for which the classifications differ will be inspected and added to the training sample with it's correct label. After we have created a sizable training sample, we will experiment with more sophisticated classifiers like stochastic gradient boosting (Chen & Guestrin 2016) and neural networks (e.g., LeCun et al 2015) which have been shown to perform better than random forest (Pashchenko et al 2018).…”
Section: Classification Of Periodic Variablesmentioning
confidence: 99%
“…Mitchell 1997;Lochner et al 2016), Neural Networks (NN Venables & Ripley 2002) and Random Forests(RF, e.g. Breiman 2001;du Buisson et al 2015;Pashchenko et al 2018).…”
mentioning
confidence: 99%
“…The machine learning has been adopted as a successful alternative approach to defining reliable objects classes, stellar types and types of variable stars (eg. Liu et al 2015;Kovács & Szapudi 2015;Krakowski et al 2016;Kuntzer et al 2016;Sarro et al 2018;Pashchenko et al 2018). It is not the first time to take advantage of this technology to classify the objects or to regress the stellar parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It finds natural patterns in data that generate insight and help us make better decisions and predictions 3 . Machine-learning algorithms have helped us to deal with complex problems in astrophysics, e.g., automatic galaxy classification (Huertas-Company et al 2008, the Morgan-Keenan spechttps://www.mathworks.com/solutions/machinelearning.html tral classification (MK; Manteiga et al 2009;Navarro et al 2012;Yi et al 2014), variable star classification (Pashchenko et al 2018) and spectral feature recognition for QSOs (Parks et al 2018).…”
mentioning
confidence: 99%